1977
DOI: 10.1021/i360064a002
|View full text |Cite
|
Sign up to set email alerts
|

Autoxidation of Aldehydes in Acetic Acid Solution

Abstract: chemical engineering since Decem.ber 1969. He studied at the same Uniuersity and obtained the degree in chemical engineering i n 1955: in 1960 he receiued the emee of doctor of tech-Zd,, , nical sciences on the subject: fading by light of anthraquinoid mordant dyes. He authored several papers, for example, in the fields ofphotoreduction of azo dyes and fading by light of organic dyes o f textiles. He is a member of the Royal Dutch Chemical Society. Pieter M. Heertjes studied at the Uniuersity of Technology, De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…For autoxidations of benzaldehyde inhibited by phenols the same kinetics and the same rate constant were found (Hendriks et al, 1977). However, it was found that at ratios of the initial Co" acetate and benzaldehyde concentrations with values >0.030 the initial oxidation rates were linear with the benzaldehyde concentration and independent of the Co" acetate and oxygen concentrations.…”
Section: Experiments and Resultssupporting
confidence: 62%
“…For autoxidations of benzaldehyde inhibited by phenols the same kinetics and the same rate constant were found (Hendriks et al, 1977). However, it was found that at ratios of the initial Co" acetate and benzaldehyde concentrations with values >0.030 the initial oxidation rates were linear with the benzaldehyde concentration and independent of the Co" acetate and oxygen concentrations.…”
Section: Experiments and Resultssupporting
confidence: 62%
“…Once they have been formed, phenylpyrucic acid ( 2 ) can be decarboxylated to produce the benzycarbonyl radical ( 8 ) in the presence of free radicals. This radical has been observed in the photolysis of dibenzylketone (Grissom, 1995), and similar radicals are produced from aldehydes during their free radical oxidation (Hendriks, van Beek, & Heertjes, 1977). The benzylcarbonyl radical ( 8 ) would then react with oxygen to produce the corresponding peroxyacid radical ( 9 ) and later the peroxyacid ( 10 ).…”
Section: Discussionmentioning
confidence: 78%
“…14 The well-established literature indicates that a formyl group readily oxidises to the corresponding carboxyl group in oxygen/ air or other oxidants, in an autoxidation cycle initiated by a radical initiator. [15][16][17][18][19][20] Benzaldehyde is one of the most common examples and more extensively studied. The autoxidation cycle is initiated by a radical initiator, which breaks the relatively weak aldehyde C-H bond (86 kcal).…”
Section: àmentioning
confidence: 99%